VARIATIONS OF CARBON ISOTOPIC RATIO OF ATMOSPHERIC CARBON DIOXIDE OVER JAPAN - ナカザワ, タカキヨ; モリモト, シンジ; アオキ, シュンジ; タナカ, マサユキ; NAKAZAWA, Takakiyo; MORIMOTO, Shinji; AOKI, Shuhji; TANAKA, Masayuki (National Institute of Polar Research, 1992)
P(論文) Carbon dioxide samples collected in the troposphere over Japan during the periods from April 1984 to November 1990 were analyzed for the carbon isotope ratio, δ^<13>C, with a precision of 0.03‰ (one standard deviation). The seasonal cycle of δ^<13>C decreased with increasing height, with a phase delay of about one month between the lower and upper troposphere, which was quite similar to that of the CO_2 concentration. It was found from the observed seasonal cycles of the CO_2 concentration and δ^<13>C that the rate of change in δ^<13>C with respect to the CO_2 concentration is about -0.05‰ per ppmv. This implies that the seasonal CO_2 cycle over Japan is mainly induced by seasonally dependent biospheric activities. However, the air transport from different latitudes is also important for the seasonal CO_2 cycle, especially in the upper troposphere. δ^<13>C decreased secularly at an average rate of about -0.03‰ per year due mainly to combustion of fossil fuels with lighter CO_2 relative to the atmospheric CO_2. Irregular variations of δ^<13>C with the periods of two or three years, superimposed on the secular trend, were also observed; they were almost in phase with these of the CO_2 concentration. From the comparison of both irregular variations, it was found that the cause could primarily attributed to the imbalance in CO_2 exchange between the atmosphere and biosphere in association with climate change, rather than between the atmosphere and oceans. departmental bulletin paper